(3EOGQI GdCYeGd GdJLGQjI GdUZjQI (B/s - (3MSf, Jhajb YHO GdQMje jhSas ((3YeGf(B: s (3OGQ GdUaGA ddfTQ hGdJhRjY(B, s, 2002)
(3eONd Gdi GdeTQhYGJ GdUZjQI(B- (3GdedcjI(B- (3JCSjS GdeTQhY GdUZjQ(B- (3eUGOQ Jehjd GdeTQhYGJ GdUZjQI(B- (3ENJjGQ GdehbY ddeTQhY GdUZjQ(B- (3GdJShjb aj GdeTQhYGJ GdUZjQI(B- (3JbOjQ MLe GdCShGb(B- (3EOGQI GdeTJQjGJ hGdeSJhOYGJ aj GdeTQhYGJ GdUZjQI(B- (3bQhV GdYedGA(B- (3GdJCejf hGdeNGWQ hGdSQbI(B-(3eMGSHI GdeTQhYGJ GdUZjQI(B- (3OhQ GdMcheI aj GdeTQhYGJ GdUZjQIs
Keywords: (3EOGQI GdCYeGds; (3GdJLGQIs; (3GdeTQhYGJs